Urban planning in two US cities through eras of rapid industrialization and de-industrialization - Detroit, Michigan, and Mobile, Alabama. - Treskow, Brigitte; Schultze, Steven (Chmielorz, 2021)
Zonierung, ein Wort und eine Vorgehen, die die Flächennutzungsplanung in amerikanischen Städten beschreibt. Sie ermöglicht eine Segregation verschiedener Landnutzungen, um Emissionen zu vermeiden. Wie funktionieren Planung und Zonierung in den USA? Ein Überblick über die Systeme, Vorschriften und Pläne, mit denen die Stadtplanung und -entwicklung gesteuert wird, weist Ähnlichkeiten und Unterschiede zum deutschen Ansatz auf. Die Bedeutung der Zonierung und der Umgang mit Zonierungsvorschriften erklärt die strikte Trennung der Landnutzung in den USA und deren Folgen. Die Fälle von Alabama und seiner Stadt „Mobile" sowie von Michigan und seiner Stadt „Detroit" verdeutlichen die unterschiedlichen Planungsansätze innerhalb der USA und die Auswirkungen dieser Ansätze auf die Bewohner.

Zoning, a word and action describing land use planning in American towns and cities, enables a segregation of different land uses in order to prevent emissions. This segregation is especially pronounced in residential areas, which are often only meant for residency and no commercial use. In many residential areas, rigid zoning regulations create environments destitute of every day supplies. Coupled with an absence of public transportation within walking distance to homes, errands by car become necessity. Also, generously sized lots lead to long walking distances. When compared to European countries, these are uniquely American problems, and an understanding of U.S. planning practices can illuminate why this is the case. How do planning and zoning work in the USA? An overview of the systems, regulations and plans used to manage urban planning and development show similarities and differences to the German approach. The importance of zoning and handling of zoning regulations explains the strict separation of land use in the USA and its consequences. The cases of Alabama and its city, "Mobile," and of Michigan and its city, "Detroit," emphasize the different approaches to planning within the USA, and the effects of these approaches on residents.
Keywords: Flächennutzungsplanung; Stadtplanung; Zonierung; Rechtsgrundlage; Städtebaurecht; Planungsprozess; Planungspraxis; Fallbeispiel; Städtevergleich